Implementation of Web Based Accounting Information System using Rapid Application Development (RAD) - husodo, calvin; Nugroho, Agus Cahyo; Widjaja, Alexandra Adriani (SISFORMA, 2024)
The purpose of the author to conduct this research is to implement an accounting information system at Mulia Shop with a website-based. In this study, the Rapid Application Development (RAD) method will be used as a system development method. There are use case diagrams that are used to describe the functions that exist in the system, flowcharts as a description of the current company and testing using black box testing to find out all functions in the system can run well. The results of this research will be an accounting information system that can assist operational activities and reports that support decision making for the owner of Toko Mulia.